Functionalization and crosslinking of microcrystalline cellulose in aqueous media: A safe and economic approach (2011)
ABSTRACT: Cellulose is the most abundant biopolymer in nature and has a broad range of applications in the pharmaceutical, food and biomedical fields. This review article describes the functionalization conditions, crosslinking agents, reaction pathways and the resulting physicochemical and mechanical properties of functionalized cellulose derivatives. The discussion is focused on aqueous reactions and crosslinking agents that render a material of low toxicity and better biodegradability with a broad range of applications. Crosslinking agents such as dialdehydes (glyoxal and glutaraldehyde), acetals (1,1,4,4-tetramethoxybutane and 1,1,5,5- tetramethoxybutane), polycarboxylic acids (acrylic, maleic, polymaleic, succinic polyitaconic and citric acids), phosphorus derivatives (phosphoric acid and triethyl phosphate), silica derivatives (tetraethoxysilane), epichlorohydrin and polyepichlorohydrin were selected for the discussion since they present a low toxicity risk and are able to react efficiently with cellulose rendering products with unique properties.